A comparative study on the distinct staygreen characteristics of two ecological types of Leymus chinensis (Poaceae) - Naren, Gaowa; Dong, Baozhu; Yu, Haoyang; Ma, Lijuan; Yang, Xu; Hao, Riqin; Wang, Xinxia; Shi, Huihui; Zhang, Lingang (Frontiers in Plant Science, 2025)
The stay-green phenotype is a valuable trait positively correlating with both forage quality and biomass production in perennial grasses. To date, with the exception of Festuca pratensis, no naturally occurring stay-green species have been reported among forage grasses. Leymus chinensis is an important forage species that presents two phenotypes: gray–green (GG) leaves and yellow–green (YG) leaves. In this study, we discovered that GG L. chinensis exhibited functional stay-green characteristics: both chlorophyll and photosynthesis were maintained at higher levels after 6 days of dark treatment, which is significantly different from that of the YG ecotype. Along with higher level of chlorophyll, GG also maintained high concentrations protein nutrient in darkness. In the case of YG, darkness significantly increased the expressions of NYC1 and NOL, which are responsible for initiating the chlorophyll degradation. However, the dark treatment did not alter the expression of NOL in the GG leaves, and the induction of NYC1 expression by darkness in GG was also significantly weaker than that observed in YG. This discrepancy could account for the slower rate of chlorophyll degradation observed in GG under dark conditions than in YG.